USURY IN THE MODERN ERA: A REVIEW OF QUR'ANIC VERSES AND HADITH - Nabilla Zalfa Azzahra (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The prohibition of usury is one of the basic teachings in Islam which is emphasized both in the Qur'an and hadith. In modern times, the practice of usury is increasingly widespread, especially through conventional financial institutions and online loan services (pinjol) that offer convenience but are often accompanied by high interest rates. This article aims to examine the law of usury according to the arguments in the Qur'an and hadith and explore its relevance to contemporary economic challenges. The discussion begins with an explanation of the definition of usury, followed by an analysis of the verses of the Qur'an and hadith that explicitly prohibit the practice, as well as the wisdom behind the prohibition of usury. The article also reviews various forms of usury that appear in modern forms, such as online loans, credit cards, and conventional banking systems. Through this study, it is hoped that it can increase understanding of the importance of implementing a sharia-based economic system that is fairer and brings blessings to Muslims.